Higher vocational college students’ learning burnout during the COVID-19 pandemic: A case study in China - Shenlong Tang; Siti Zuraidah Md Osman (Institute of Advanced Engineering and Science, 2023)
This study examines students’ levels of learning burnout during the COVID-19 pandemic. Learning burnout levels were also investigated about students’ gender, hometown, family member structure, and field of major. The study employs a random sampling survey method, with 1,098 students from a public higher vocational college in Shandong Province, China. The collected data was analyzed using SPSS 26. The results found that 71.5% of students are at a moderate burnout level, 27.0% are at a low level, and only 1.5% are at a high level, and there was no high level of learning burnout on a single item during the COVID-19 pandemic. The data showed that the levels of learning burnout of male students, students who live in town, non-only child students, and students majoring in science and engineering were higher than the other group of students. There was a statistically significant difference in the level of student learning burnout by gender, but not in the variables of hometown, family structure, or field of major. Although studies show that students’ learning burnout level is not affected by COVID-19, students generally have learning burnout. Therefore, three strategies were also put forward to reduce students' learning burnout from school.